I Am Helpful - Capozzi, Suzy; Unten, Eren Blanquet (New York, NY : Rodale Kids, 2018)
"When a new baby sister arrives, one little girl has a lot to adjust to. However, by helping her parents and taking on special jobs like singing to the baby, she learns that being a big sister comes with big rewards (plus a little spit-up too)."--Page [4] of cover.
new kids book 2022 fall.
310L
Decoding demand: 62 (high) Semantic demand: 45 (medium) Syntactic demand: 34 (low) Structure demand: 81 (very high)
Keywords: Helping behavior in children -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Infants -- Juvenile fiction; Families -- Juvenile fiction; Children -- Conduct of life; Helping behavior in children; Helpfulness -- Juvenile fiction; Behavior -- Juvenile fiction; Fiction; Juvenile works; Readers (Publications)